Model technical and tactical training karate «game» manner of conducting a duel - Natalya Boychenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: optimization of technical and tactical training karate «gaming» the manner of conducting a duel. Material and Methods: analysis and compilation of scientific and methodological literature, interviews with coaches for shock combat sports, video analysis techniques, teacher observations. Results: the model of technical and tactical training karate «game» manner of conducting a duel. Selection was done complexes jobs matching techniques to improve athletes 'game' in the manner of conducting a duel «Kyokushin» karate. Conclusion: the model of technical and tactical training fighters "game" manner of conducting a duel, which reveals the particular combination technique karate style «Kyokushin». Selection was done complexes jobs matching techniques to improve athletes 'game' in the manner of conducting a duel «Kyokushin» karate, aimed at improving the combinations with the action on the response of the enemy.